Bilateral Wallerian degeneration of the middle cerebellar peduncles due to paramedian pontine infarction: MRI findings. - Küker, W; Schmidt, F; Heckl, S; Nägele, T; Herrlinger, U (2004)
Wallerian degeneration is a frequent finding in lesions of the pyramidal tract, but has been observed after damage of the other fibre systems as well. Few reports exist about Wallerian degeneration of cerebellar fibres after distant lesions to the axons. Here, we report on a patient who developed degeneration of both middle cerebellar peduncles after a paramedian pontine infarction.